2014
DOI: 10.1371/journal.pone.0101837
|View full text |Cite
|
Sign up to set email alerts
|

Neural Manifestations of Implicit Self-Esteem: An ERP Study

Abstract: Behavioral research has established that humans implicitly tend to hold a positive view toward themselves. In this study, we employed the event-related potential (ERP) technique to explore neural manifestations of positive implicit self-esteem using the Go/Nogo association task (GNAT). Participants generated a response (Go) or withheld a response (Nogo) to self or others words and good or bad attributes. Behavioral data showed that participants responded faster to the self paired with good than the self paired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 69 publications
6
16
1
Order By: Relevance
“…The current study extended our understanding by revealing that implicit self-evaluation moderates N200 amplitudes, which suggests that self-associative information actually manifests before 300 ms. This idea is in line with one of our studies assessing automatic self-evaluation (Wu et al, 2014) as well as previous studies examining implicit evaluations of other social targets such as age judgments (van der Lugt et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current study extended our understanding by revealing that implicit self-evaluation moderates N200 amplitudes, which suggests that self-associative information actually manifests before 300 ms. This idea is in line with one of our studies assessing automatic self-evaluation (Wu et al, 2014) as well as previous studies examining implicit evaluations of other social targets such as age judgments (van der Lugt et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies using implicit association task (of which the logic is the same with IAT) indicated that implicit attitudes were activated by the presentation of category words rather than attribute words (Banfield, van der Lugt, & Münte, 2006;Bosson, Swann, & Pennebaker, 2000;van der Lugt, Banfield, Osinsky, & Münte, 2012). This idea is confirmed by one of our studies using GNAT to measure the implicit self-evaluation (Wu et al, 2014). Specifically, in this study, participants generated a response (Go) or withheld a response (Nogo) to self or others words and good or bad attributes.…”
Section: Eeg Recording and Data Analysissupporting
confidence: 85%
“…Our result, therefore, suggests that the control participants might more efficiently categorize the self‐positivity pairings compared to the self‐negativity pairings. Together with the previous findings, we thus provide additional electrophysiological evidence on the implicit self‐positivity bias among healthy individuals (Chen et al., 2014; Egenolf et al., 2013; Wu et al., 2014).…”
Section: Discussionsupporting
confidence: 84%
“…Considerable studies have used various methodologies such as the implicit association test (IAT), Go/Nogo association (GNAT) and name letter evaluations to explore the implicit self-esteem (Greenwald and Banaji, 1995;Greenwald and Farnham, 2000;Greenwald et al, 2002;Wu et al, 2014;Grundy et al, 2015). Moreover, the implicit and explicit self-esteem have been considered to be different constructs, and they might have different influences on cognitive processing or social behavior (Greenwald and Banaji, 1995;Bosson et al, 2000;Greenwald and Farnham, 2000).…”
Section: Discussionmentioning
confidence: 99%